TOURISM: THE EFFECT OF INTENTION AND INNOVATION ON TOURIST LOYALTY MEDIATED BY TOURISM ACCESS - Putu Ananda Devi Nugraha; Nur Wahyuningsih, Andi; Putu Suciyawati, Ni (Journal of Institution and Sharia Finance, 2025)
This study aims to determine the effect of tourism access and product innovation on tourist loyalty with tourist satisfaction as a mediator. The sample used in this study was 100 respondents who were tourists visiting an area. Data were collected using purposive sampling and the Partial Least Square (PLS) analysis method to determine the influence of the variables involved. The results of this study indicate whether or not access and product innovation have an effect on tourist loyalty. The better the tourism access and product innovation, the higher the tourist satisfaction, and the stronger the tourist loyalty.